Highly efficient electrochemiluminescence of nitrogen-doped carbon quantum dots - Xiaoli Qin; Congyang Zhang; Zackry Whitworth; Ziying Zhan; Kenneth Chu; Ping Hu; Sara Jahanghiri; Jigang Zhou; Jinxing Chen; Qiao Zhang; Zhifeng Ding (Advanced Sensor and Energy Materials, 2023)
Nitrogen-doped carbon quantum dots (N-CQDs) are nanocomposites that can be synthesized by the hydrothermal method. In this work, N-CQDs with the size of 3.2 ± 1.7 nm was prepared from 1 g citric acid and 2 g urea precursor in 10 mL water. Electrochemiluminescence (ECL) of the prepared N-CQDs with K2S2O8 as a coreactant was found to reach a high ECL efficiency up to 109% relative to that of the Ru(bpy)32+/K2S2O8, coreactant system, revealing their great potential for electroanalysis. It is probably because that N elements were doped well in this N-CQDs and increased presence of surface states per mass of N-CQDs. From the spooling ECL spectroscopy, it can be found that the ECL spectra exhibited both a red shift compared with their photoluminescence (PL) spectrum and a wavelength shift during the potentiodynamic scan in the ECL evolution and devolution processes, due to various emissive excited states of N-CQDs leading to higher ECL efficiency. This work gives an insight into development of high ECL efficiency N-CQDs for bioanalytical and light emitting applications.